Association of muscles length and strength with balance and functional status among children with diplegic spastic cerebral palsy - Afnan, Zavata; Malik, Arshad Nawaz; Jahan, Saira; Ali, Arshad (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the correlation of muscle length and muscle strength with balance and functional status among children with diplegic spastic cerebral palsy. Method: The cross-sectional study was conducted from February to July 2021 at the Physical Therapy Department of Chal Foundation and Fatima Physiotherapy Centre, Swabi, Pakistan, and comprised children aged 4-12 years with diplegic spastic cerebral palsy. The strength of back and lower limb muscles was assessed through manual muscles testing. Lower limb muscle’s length, indicating tightness, was assessed using goniometer. Paediatric balance scale and gross motor function measure scale-88 were used to assess balance and gross motor function. Data was analysed using SPSS 23. Results: Of the 83 subjects, 47(56.6%) were boys and 36(43.4%) were girls. The overall mean age was 7.31±2.02 years, mean weight was 19.71±5.45kg, mean height was 105.5±14cm and mean body mass index was 17.32±1.64 kg/m2. There was a positive and significant correlation of all the lower limb muscles’ strength with balance (p<0.01) and functional status (p<0.01). The correlation between the tightness of muscles and balance was significant and negative for all lower limb muscles (p<0.005). The correlation between the muscles’ tightness and functional status was negative and significant for all lower limb muscles (p<0.005). Conclusion: Good muscle strength and appropriate flexibility of lower limb muscles enhanced functional status and good balance in children with diplegic spastic cerebral palsy. Key Words: Balance, Cerebral palsy, Diplegic cerebral palsy, Functional status, Muscle length, Muscle strength.